Graph transformation : 8th International Conference, ICGT 2015, held as part of STAF 2015, L'Aquila, Italy, July 21-23, 2015. Proceedings /: 8th International Conference, ICGT 2015, held as part of STAF 2015, L'Aquila, Italy, July 21-23, 2015. Proceedings. (2015) - Unknown
No abstract available